2021
DOI: 10.1021/acsami.1c21489
|View full text |Cite
|
Sign up to set email alerts
|

Fast Customization of Microneedle Arrays by Static Optical Projection Lithography

Abstract: Customized microneedle arrays (CMNAs) hold great promise for precise transdermal delivery in a minimally invasive manner. Currently, the fast customization of microneedle arrays remains a great challenge. Here, we show a static optical projection lithography (SOPL) technology for fast 3D printing CMNAs. In this technology, the digital light is statically projected to induce the spatial polymerization of monomer solutions, and therefore microneedle formation can be precisely controlled by the intensity distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, the common 3D printing technology available on the market with low precision and a rough surface is far from meeting the processing requirements of the microneedle patch. As shown in Figure f, Gou and co-workers proposed a 3D-printing technology, named static optical projection lithography (SOPL), for quickly fabricating MNAs in seconds . On the basis of the spatial distribution of projected digital light, this technology enabled fast fabrication without the need for molding or multiple printing.…”
Section: Microneedle Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the common 3D printing technology available on the market with low precision and a rough surface is far from meeting the processing requirements of the microneedle patch. As shown in Figure f, Gou and co-workers proposed a 3D-printing technology, named static optical projection lithography (SOPL), for quickly fabricating MNAs in seconds . On the basis of the spatial distribution of projected digital light, this technology enabled fast fabrication without the need for molding or multiple printing.…”
Section: Microneedle Fabrication Methodsmentioning
confidence: 99%
“…Reprinted from Liu, X.; Li, R.; Yuan, X.; Yang, L.; Luo, J.; Jiang, X.; Gou, Z.; Li, B.; Jiang, X.; Gou, M. Fast Customization of Microneedle Arrays by Static Optical Projection Lithography. ACS Applied Materials & Interfaces 2021 , 13 (50), 60522–60530 . Copyright 2021 American Chemical Society.…”
Section: Microneedle Fabrication Methodsmentioning
confidence: 99%
“…Regarding hair loss treatment, some studies have shown that drug-free microneedles can remodel the perifollicular microenvironment in the balding region and then induce hair regeneration [8,9]. In addition, the specific distribution of microneedles can deliver substances to specific locations [10,11]. Based on these reports, we propose a hypothesis that the customized MNA can locally modulate the dermal microenvironment and then precisely promote the hair regeneration in situ.…”
Section: Introductionmentioning
confidence: 90%
“…3D printing can be used for the flexible customization of MNA with a fine structure and personalized shape [12,13]. Recently, our group developed a 3D printing technology, static optical projection lithography (SOPL), for flexibly customizing MNA, which can rapidly construct customized MNA within seconds through the spatial polymerization of monomer solution induced by static projected digital light [11,14]. Here, SOPL technology was used to quickly fabricate MNAs with designed shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Together, it remains a challenge to rapidly fabricate high-quality HMNs. Nonetheless, our group developed a 3D printing technology, namely static optical projection lithography (SOPL), for rapid customizing high-quality solid microneedle arrays[ 22 ]. The obtained solid microneedles do not have the stair-like surface and layer-by-layer structure that are associated with the common 3D-printing technologies.…”
Section: Introductionmentioning
confidence: 99%